Increased frequency of freeze-thaw events in a future climate can significantly increase negative effects of copper on enchytraeids - Boas, Sara W.; Slotsbo, Stine; Patricio Silva, Ana L.; Larsen, Martin M.; Damgaard, Christian; Holmstrup, Martin (Applied Soil Ecology, 2016)
Many anthropogenic activities negatively affect the environment and stress the organisms living there. Metals are some of the most common contaminants in temperate climate soils, and recent mining activities in subarctic and arctic regions further emphasize the need for focus on the environmental impact in cold climate regions. The present study investigated how the combination of sub-zero temperatures and copper (Cu) contamination of soil affected the freeze tolerant oligochaete worm, Enchytraeus albidus. Worms were exposed to one of three temperature treatments (constant +1.5 °C, constant −6 °C, or repeated daily cycles between +1.5 to −6 °C) in combination with one of several different Cu (CuCl 2 ) concentrations in soil. The results showed that concentrations of Cu that are sublethal under benign temperatures (+1.5 °C) caused a reduced cold tolerance of worms. We estimated that LC50 values for Cu were 470 μg Cu g −1 dry soil at +1.5 °C, 300 μg Cu g −1 dry soil at constant −6 °C, but only 95 μg Cu g −1 dry soil after exposure to repeated daily freezing and thawing (+1.5 to −6 °C). Levels of the main cryoprotectant of these worms, glucose, were significantly lower in worms exposed to elevated Cu, which may have contributed to the reduced cold tolerance. These results imply that detrimental effects of Cu in the environment may be considerably worse in a cold environment where freezing and thawing of the habitat occurs on a regular basis than in a climate with periods of constant freezing, or in a temperate climate where freezing of soils never takes place.